Teachers' Acceptance of Canva Web-Based Multimodal Digital Media in Deep Learning Approach in Cileunyi District: Based on SUS - Nurrani, Nisya; Kurniawan, Dede Trie; Abidin, Yunus (International Conference on Elementary Education, 2025)
The rapid development of technology has given rise to a generation of digital natives who are accustomed to the virtual world since birth. This phenomenon requires a transformation in teaching methods at the primary and secondary education levels in Indonesia. More in-depth learning, which can be implemented through a deep learning approach, as well as the use of Canva web-based multimodality media offers great potential as a solution to improve the quality of education that suits the characteristics of this generation and is in line with the philosophy of the Merdeka Curriculum. This research focuses on evaluating the level of acceptance of multimodality learning media developed using the Canva web platform, which is specifically designed to facilitate deep learning among elementary school educators. To achieve this goal, a survey method was used with a System Usability Scale (SUS) questionnaire instrument distributed to 90 teachers located in Bandung Regency. Analysis of the collected data shows that the average SUS score is 70.72. Based on the SUS scale, this score indicates that the learning media is in the "acceptable" category, with a score of "C" and a qualitative description of "Good". This result implies that Canva web-based multimodality digital media is generally well received by teachers at the primary school level. Nevertheless, a continuous process of evaluating and improving the quality of the media is considered important to maximize its benefits and enhance the user experience according to their needs and expectations.